Light-scattering detection with a fluorimetric detector in high-performance liquid chromatography - Takeuchi, T.; Lim, L.W.; Inui, A.; Yamada, T.; Aspanut, Z. (2007)
Non-fluorescence compounds were detected by a fluorescence detector based on scattering light. The fluorescence detector was used without any modification, and the scattering light was observed at the wavelength twice as long as the excitation wavelength. Actually the wavelength of the observed scattering light was the same as that of the excitation light. The maximum signal was achieved at around 280 nm. The signal was increased with increasing molecular weight or size of analytes. Colloidal silica with nanometer sizes, ethylene glycol oligomers, saccharides and cyclodextrins could be visualized by the present detection method. The detection limit at S/N=3 for colloidal silica with 78 mn was 39 pg for 20-mu L injection. (c) 2007 Published by Elsevier B.V.